Radiographic Anatomical Studies on the Fusion of Ossification Centres in the Developing Radius, Ulna, Carpals, Metacarpals and Phalanges of Right Forelimb in Different Breeds of Dog (Canis familiaries) - Charjan, R. Y.; Sathapathy, S.; Banubakode, S. B.; Joshi, S. K. (Indian Journal of Veterinary Anatomy, 2015)
The present study was carried out on the 18 pups of German Shepherd, Pomeranian and non- descript dogs, six each from different litters of either sex and of known age to study the radiographic anatomy on the fusion of ossification centres in the developing radius, ulna, carpals, metacarpals and phalanges at 15, 30, 45, 60, 90, 120, 150 and 180 days of age, respectively. It was found that the radius and ulna developed from three principal ossification centres. The proximal and the distal epiphyses of both radius and ulna remained separated from thediaphysis up to the age of 180 days in all the breeds. The carpal bones were developed from ten centres of ossification with the centre for the body of accessory carpal bone was the first to appear and centre for epiphysis of accessory carpal bone was the last to appear amongst the carpus region in all the three breeds. Each metacarpal bone in all the breeds was developed from two centres of ossification. Proximal and distal phalanges of each digit developed from two centers.